3D bioprinted glioma stem cells for brain tumor model and applications of drug susceptibility. (10th October 2016) - Dai, Xingliang; Ma, Cheng; Lan, Qing; Xu, Tao
Abstract: Glioma is still difficult to treat because of its high malignancy, high recurrence rate, and high resistance to anticancer drugs. An alternative method for research of gliomagenesis and drug resistance is to use in vitro tumor model that closely mimics the in vivo tumor microenvironment. In this study, we established a 3D bioprinted glioma stem cell model, using modified porous gelatin/alginate/fibrinogen hydrogel that mimics the extracellular matrix. Glioma stem cells achieved a survival rate of 86.92%, and proliferated with high cellular activity immediately following bioprinting. During the in vitro culture period, the printed glioma stem cells not only maintained their inherent characteristics of cancer stem cells (Nestin), but also showed differentiation potential (glial fibrillary acidic protein and β -tubulin III). In order to verify the vascularization potential of glioma stem cells, tumor angiogenesis biomarker, vascular endothelial growth factor was detected by immunohistochemistry, and its expression increased from week one to three during the culture period. Drug-sensitivity results showed that 3D printed tumor model was more resistant to temozolomide than 2D monolayer model at TMZ concentrations of 400–1600 μ g ml −1 . In summary, 3D bioprinted glioma model provides a novel alternative tool for studying gliomagenesis, glioma stem cell biology, drug resistance, and anticancer drug susceptibility in vitro .